Nurses’ Knowledge and Compliance with Intravenous Insertion Standard Operating Procedures in Emergency Care Settings - Rahman, Abdur; Fauzi, Ahmad Kholid (Fakultas Kesehatan, Universitas Nurul Jadid, 2025)
Background: The emergency department is the main entry point for hospital services and plays a crucial role in providing immediate patient care. Intravenous insertion is a common invasive procedure that may contribute to nosocomial infections if standard operating procedures (SOPs) are not properly followed. Nurses’ compliance with SOPs is therefore essential for infection prevention and patient safety. Objective: This study aimed to examine the relationship between nurses’ knowledge levels and compliance with intravenous insertion standard operating procedures in emergency care settings. Methods: A correlational study with a cross-sectional design was conducted in January 2016. The study involved all nurses working in the emergency department, with a total of 18 participants selected using total sampling. Data were collected using structured questionnaires to assess knowledge and observational checklists to evaluate compliance. Statistical analysis was performed using Spearman’s rho test with a significance level of 5% (α = 0.05). Results: The analysis revealed a statistically significant relationship between nurses’ knowledge levels and compliance with intravenous insertion SOPs (p = 0.001), indicating that higher knowledge levels were associated with better compliance. Conclusion: Nurses’ knowledge is a key determinant of compliance with intravenous insertion SOPs and plays an important role in preventing nosocomial infections in emergency care settings.